The Horse Image in The Story “Donan” By Turob Tula (Eurasian Research Bulletin, 2022)
Among animals, horse is referred as an important animal of various usage. In world folklore and literary criticism, the poetics of the image, the English folklore of the image of the horse, the coverage of the historical foundations of literature are constantly attracting attention. In particular, it is significant to examine the symbolic meaning of this image in fiction, its personification, as well as horse is very close to human in terms of virtue.